Investigation about the copper adsorption on the chloropropylsilica gel surface modified with a nanostructured dendrimer DAB-Am-16: an analytical application for determination of copper in different samples - Carmo, Devaney Ribeiro do [UNESP] (2013)
The third generation (G-3) poly(propyleneimine)hexadecaamine dendrimer (DAB-Am-16) was grafted onto the chloropropylsilica gel surface (DPPIPS). The modified silica (DPPIPS) was characterized by Electronic (Uv-Vis), vibrational and Electron Paramagnetic Resonance (EPR), spectrocopies, surface area (331.07 m².g-1) and porosity analyses (pore diameter of 41.9 nm) and cyclic voltammetry technique. The copper adsorption studies were performed using a batchwise process and the DPPIPS showed adsorption capacities of 16.3, 47.8 and 659.5 mol.g-1 in aqueous, ethanol and acetone medium, respectively, with recoveries close to 100% after percolation with HCl 1.0 mol.L-1. The results suggest that the sorption of copper ions on DPPIPS occurs mainly by surface complexation and a Langmuir model allowed describing the sorption of the metal ions on DPPIPS. As an application of this chemically modified material, copper was determined in real samples of distilled spirits and fuel alcohol.